Molecular Mechanisms of Human Disease Mediated by Oncogenic and Primary Immunodeficiency Mutations in Class IA Phosphoinositide 3-Kinases - Dornan, Gillian L.; Burke, John E. (Frontiers in Immunology, 2018)
The signalling lipid phosphatidylinositol 3,4,5, trisphosphate (PIP3) is an essential mediator of many vital cellular processes, including growth, survival, and metabolism. PIP3 is generated through the action of the class I phosphoinositide 3-kinases (PI3K), and their activity is tightly controlled through interactions with regulatory proteins and activating stimuli. The class IA PI3Ks are composed of three distinct p110 catalytic subunits (p110 alpha, p110 beta, p110 delta) and they play different roles in specific tissues due to disparities in both expression and engagement downstream of cell surface receptors. Disruption of PI3K regulation is a frequent driver of numerous human diseases. Activating mutations in the PIK3CA gene encoding the p110 alpha catalytic subunit of class IA PI3K are frequently mutated in several cancer types, and mutations in the PIK3CD gene encoding the p110 delta catalytic subunit have recently been identified in primary immunodeficiency patients. All class IA p110 subunits interact with p85 regulatory subunits, and mutations/deletions in different p85 regulatory subunits have been identified in both cancer and primary immunodeficiencies. In this review, we will summarize our current understanding for the molecular basis of how class IA PI3K catalytic activity is regulated by p85 regulatory subunits, and how activating mutations in the PI3K catalytic subunits PIK3CA, PIK3CD (p110 alpha, p110 delta) and regulatory subunits PIK3R1 (p85 alpha) mediate PI3K activation and human disease.